2018
DOI: 10.3389/fimmu.2018.00126
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Influenza Infection with Circulating Strains to Test Seasonal Vaccine Efficacy

Abstract: Influenza virus infection is a significant cause of morbidity and mortality worldwide. The surface antigens of influenza virus change over time blunting both naturally acquired and vaccine induced adaptive immune protection. Viral antigenic drift is a major contributing factor to both the spread and disease burden of influenza. The aim of this study was to develop better infection models using clinically relevant, influenza strains to test vaccine induced protection. CB6F1 mice were infected with a range of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…The rapid increase in the IgG2a antibody isotype in cGAMP/Quil-A adjuvanted groups that we observed was also consistent with a Th-1 bias of adjuvant action mode (54). We have found that in aged mice, cGAMP potentiated the protective immune response in the presence of Quil-A, while in adult mice Quil-A alone efficiently increased survival and HAI titers, and further addition of 1-5 µg cGAMP did not significantly increase the high protective efficacy of the A/California07/09 H1N1vaccine (55).…”
Section: Discussionsupporting
confidence: 88%
“…The rapid increase in the IgG2a antibody isotype in cGAMP/Quil-A adjuvanted groups that we observed was also consistent with a Th-1 bias of adjuvant action mode (54). We have found that in aged mice, cGAMP potentiated the protective immune response in the presence of Quil-A, while in adult mice Quil-A alone efficiently increased survival and HAI titers, and further addition of 1-5 µg cGAMP did not significantly increase the high protective efficacy of the A/California07/09 H1N1vaccine (55).…”
Section: Discussionsupporting
confidence: 88%
“…Influenza preclinical studies using mice require a dose of 1.5 µg HA and a maximum volume of injection of 100 µL . Therefore, the target concentration that should be achieved is 15 µg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…For coronaviruses, Calu-3 or Vero E6 cells are often used for similar reasons, but again differ by species, cell source, disease state, and innate antiviral signaling pathways [12,13] compared to normal, healthy human conducting airway and alveolar epithelium [14], thus providing an insufficient model. Unfortunately, complications also exist within animal models of IAV, not only in mice, rats, and guinea pigs, but even in more human-relevant options for evaluation such as ferrets and macaques [15,16]. These models often require species-adapted viral strains, and fail to recapitulate features of human innate antiviral responses and clinical symptoms of infection [17,18].…”
Section: Introductionmentioning
confidence: 99%